Air ionization as a control technology for off-gas emissions of volatile organic compounds. (June 2017) - Kim, Ki-Hyun; Szulejko, Jan E.; Kumar, Pawan; Kwon, Eilhann E.; Adelodun, Adedeji A.; Reddy, Police Anil Kumar
Abstract: High energy electron-impact ionizers have found applications mainly in industry to reduce off-gas emissions from waste gas streams at low cost and high efficiency because of their ability to oxidize many airborne organic pollutants ( e.g ., volatile organic compounds (VOCs)) to CO2 and H2 O. Applications of air ionizers in indoor air quality management are limited due to poor removal efficiency and production of noxious side products, e.g., ozone (O3 ). In this paper, we provide a critical evaluation of the pollutant removal performance of air ionizing system through comprehensive review of the literature. In particular, we focus on removal of VOCs and odorants. We also discuss the generation of unwanted air ionization byproducts such as O3, NOx, and VOC oxidation intermediates that limit the use of air-ionizers in indoor air quality management. Graphical abstract: Highlights: Much research effort has been put to eliminate or reduce airborne pollutants. Destructive methods of VOCs commonly involve thermal oxidation with or without a catalyst. In this review, we provide insights into effective strategy for air quality remediation. To this end, we assessed the role of air ionization methods for the control of IAQ. We discuss future opportunities for air ionization techniques as reliable tools for controlling VOCs. Abstract : Performance of air ionization techniques is assessed as reliable tools for controlling VOCs and odors to meet IAQ standards.